Focal epithelial hyperplasia by human papillomavirus (HPV)‐32 misdiagnosed as HPV‐16 and treated with combination of retinoids, imiquimod and quadrivalent HPV vaccine. Issue 12 (5th June 2015) - Gemigniani, Franco; Hernández‐Losa, Javier; Ferrer, Berta; García‐Patos, Vicente
Abstract: Focal epithelial hyperplasia (FEH) or Heck's disease is a rare, benign and asymptomatic mucosal proliferation associated with human papillomavirus (HPV) infection, mainly with genotypes 13 and 32. We report a florid case of FEH in an 11‐year‐old Haitian girl with systemic lupus erythematosus receiving immunosuppressive therapy. Cryotherapy was previously performed on numerous occasions with no results. We decided to prescribe a non‐invasive and more comfortable treatment. A combination of topical retinoid and imiquimod cream was well tolerated and led to an important improvement. The evidence of infection by HPV‐16 detected by polymerase chain reaction (PCR) technique, prompted us to prescribe the quadrivalent HPV vaccine (types 6, 11, 16 and 18). Subsequent PCR sequencing with generic primers GP5–GP6 and further BLAST comparative analysis confirmed that genomic viral sequence in our case truly corresponded with HPV‐32. This molecular misdiagnosis can be explained by the similarity between genomic sequences of both HPV‐16 and ‐32 genotypes. At the 1‐year follow up, we observed total clinical improvement and no recurrences of the disease. Complete healing in this case may correspond to a potential action of topical retinoid, imiquimod and the cross‐protection mechanism of the quadrivalent HPV vaccine.